2005
DOI: 10.1037/0097-7403.31.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Recovery From Forward and Backward Blocking.

Abstract: This article demonstrates and analyzes spontaneous recovery of stimulus control following both forward and backward blocking in a conditioned suppression preparation with rats. Experiment 1 found, in first-order conditioning, robust forward blocking and an attenuation of it following a retention interval. Experiment 2 showed, in sensory preconditioning, recovery of responding following both forward and backward blocking. Also, the results of this experiment indicated that response recovery to the blocked stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
5
35
0
1
Order By: Relevance
“…The SOCR model (as the extended comparator hypothesis, which serves as its basis) has trouble to explain changes in responding to a CS as function of passage of time. Specifically, the SOCR model fails to explain relevant findings in the stimulus competition literature, such as spontaneous recovery of responding after overshadowing (Kraemer, Lariviere, & Spear, 1988) or blocking (Pineño, Urushihara, & Miller, 2005). The problem of the SOCR model is, not only that there is no mechanism by which passage of time could affect responding to a CS, but also that there is no obvious reason why the mechanisms already existing in the model should be affected by passage of time.…”
Section: Some Effects the Response Rule Can Explain (But Socr Cannot)mentioning
confidence: 73%
“…The SOCR model (as the extended comparator hypothesis, which serves as its basis) has trouble to explain changes in responding to a CS as function of passage of time. Specifically, the SOCR model fails to explain relevant findings in the stimulus competition literature, such as spontaneous recovery of responding after overshadowing (Kraemer, Lariviere, & Spear, 1988) or blocking (Pineño, Urushihara, & Miller, 2005). The problem of the SOCR model is, not only that there is no mechanism by which passage of time could affect responding to a CS, but also that there is no obvious reason why the mechanisms already existing in the model should be affected by passage of time.…”
Section: Some Effects the Response Rule Can Explain (But Socr Cannot)mentioning
confidence: 73%
“…Second, there are other instances of recovery from decremental procedures with the passage of time. For instance, Kraemer, Lariviere, and Spear (1988) and Pineño, Urushihara, and Miller (2005) have reported that with the passage of time there is recovery from the adverse effects of overshadowing and blocking, respec- tively. Those results differ from the present ones in that overexpectation involves the depression of a previously well-conditioned stimulus, rather than the attenuation of initial conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that B is absent in the second phase, it loses strength. Typically, however, the amount of reduction in backward blocking is weaker than the amount of reduction in forward blocking (see e.g., Beckers, De Houwer, Pineño, & Miller, 2005;Kruschke & Blair, 2000;Lovibond, Been, Mitchell, Bouton, & Frohardt, 2003;Pineño, Urushihara, & Miller, 2005;Shanks, 1985). This asymmetry in strengths of forward and backward blocking is a trialorder effect that is challenging for extant time-independent Bayesian approaches.…”
Section: Application To Blocking and Backward Blockingmentioning
confidence: 99%